2020
DOI: 10.3390/coatings10080727
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Doped Hydroxyapatite-Based Coatings Obtained by Pulsed Galvanostatic Electrochemical Deposition with Adjustable Electrochemical Behavior

Abstract: The aim of this study was to adapt the electrochemical behavior in synthetic body fluid (SBF) of hydroxyapatite-based coatings obtained by pulsed galvanostatic electrochemical deposition through addition of Mg in different concentrations. The coatings were obtained by electrochemical deposition in a typical three electrodes electrochemical cell in galvanic pulsed mode. The electrolyte was obtained by subsequently dissolving Ca(NO3)2·4H2O, NH4H2PO4, and Mg(NO3)2·6H2O in ultra-pure water and the pH value was set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 64 publications
0
29
0
1
Order By: Relevance
“…The electrodeposition was controlled using a multichannel Potentiostat/Galvanostat (Parstat MC, Princeton Applied Research-Ametek, Oak Ridge, TN, USA) operating in pulsed galvanostatic mode. One pulse consisted of an activation stage (i ON = −0.85 mA/cm 2 for 1 s), followed by a relaxation stage (i OFF = 0 mA/cm 2 for 1 s) [42]. In total, 1200 pulses were applied.…”
Section: Coating Depositionmentioning
confidence: 99%
“…The electrodeposition was controlled using a multichannel Potentiostat/Galvanostat (Parstat MC, Princeton Applied Research-Ametek, Oak Ridge, TN, USA) operating in pulsed galvanostatic mode. One pulse consisted of an activation stage (i ON = −0.85 mA/cm 2 for 1 s), followed by a relaxation stage (i OFF = 0 mA/cm 2 for 1 s) [42]. In total, 1200 pulses were applied.…”
Section: Coating Depositionmentioning
confidence: 99%
“…The protection efficiency (P e ) was calculated taking into account the corrosion current values of the coated samples and the uncoated MgCa1 68,69 with the following formula The results show that by Zn and Ga addition into CaP composition, the protection efficacy was increased, reaching a value of P e = 99.7%, the highest among coated variants, in the case of MgCa1/(CaP+Ga) (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…The protection efficiency ( P e ) was calculated taking into account the corrosion current values of the coated samples and the uncoated MgCa1 , with the following formula …”
Section: Resultsmentioning
confidence: 99%
“…Doping the HA coatings with Mg changed the properties. They facilitated the control of the dissolution rate of the HA coatings ( Vranceanu et al, 2020 ). Our previous research showed that the duration of ED of 20 min for the fabrication of HA coatings on 3D printed Ti scaffolds can promote cell viability, proliferation and osteogenic gene expression of MC3T3-E1 ( Zhu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%